OBSERVATIONS OF OUTFLOWING ULTRAVIOLET ABSORBERS IN NGC 4051 WITH THE COSMIC ORIGINS SPECTROGRAPH - Kraemer, S; Crenshaw, D; Dunn, J; Turner, T; Lobban, A; Miller, L; Reeves, J; Fischer, T; Braito, V (2012)
We present new Hubble Space Telescope (HST)/Cosmic Origins Spectrograph (COS) observations of the narrow-line Seyfert 1 galaxy NGC4051. These data were obtained as part of a coordinated observing program including X-ray observations with the Chandra/High Energy Transmission Grating (HETG) spectrometer and Suzaku. We detected nine kinematic components of UV absorption, which were previously identified using the HST/Space Telescope Imaging Spectrograph (STIS). None of the absorption components showed evidence for changes in column density or profile within the 10 yr between the STIS and COS observations, which we interpret as evidence of (1) saturation, for the stronger components, or (2) very low densities, i.e., n H < 1 cm-3, for the weaker components. After applying a +200 km s-1 offset to the HETG spectrum, we found that the radial velocities of the UV absorbers lay within the O VII profile. Based on photoionization models, we suggest that, while UV components 2, 5, and 7 produce significant O VII absorption, the bulk of the X-ray absorption detected in the HETG analysis occurs in more highly ionized gas. Moreover, the mass-loss rate is dominated by high-ionization gas which lacks a significant UV footprint. © 2012. The American Astronomical Society. All rights reserved..